2006
DOI: 10.4310/mrl.2006.v13.n6.a6
|View full text |Cite
|
Sign up to set email alerts
|

An upper estimate of integral points in real simplices with an application to singularity theory

Abstract: Abstract. Let ∆(a 1 , a 2 , · · · , an) be an n-dimensional real simplex with vertices at ··· ,an) be the number of positive integral points lying in ∆(a 1 , a 2 , · · · , an). In this paper we prove that n!P (a 1 ,a 2 ,··· ,an) ≤ (a 1 − 1)(a 2 − 1) · · · (an − 1). As a consequence we have proved the Durfee conjecture for isolated weighted homogeneous singularities: n!pg ≤ µ, where pg and µ are the geometric genus and Milnor number of the singularity, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
0
21
0
Order By: Relevance
“…The weak version was finally proved by Yau and Zhang [20]. In the same paper, the authors claim the strong version has been checked computationally up to n ≤ 10.…”
Section: A First Application: a Bound "á La Wilf "mentioning
confidence: 90%
“…The weak version was finally proved by Yau and Zhang [20]. In the same paper, the authors claim the strong version has been checked computationally up to n ≤ 10.…”
Section: A First Application: a Bound "á La Wilf "mentioning
confidence: 90%
“…They are sharp because the equality holds true if and only if all ai take the same integer. The weak estimate in has recently been proven true by the authors of . Before that, , , , showed that holds for 3n5.…”
Section: Introductionmentioning
confidence: 90%
“…The GLY conjecture was proven by Xu and Yau for n = 3 [20] and n = 4 [22], for n = 5, see [4], [6] and [8], Wang and Yau for 3 ≤ n ≤ 6 [18], where β(n) = n − 1 for 3 ≤ n ≤ 6. The rough GLY upper estimate for all n was proven in [24].…”
Section: Where Equality Holds If and Only Ifmentioning
confidence: 97%
“…The GLY conjecture was the first major step towards proving the following conjecture made by Yau in 1995 [24]:…”
Section: Theorem 13 (Lu-ya-zu [11]mentioning
confidence: 99%